2010
DOI: 10.1590/s0100-736x2010001100007
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição do vírus rábico no sistema nervoso central em ruminantes naturalmente infectados

Abstract: With the aim to study the distribution of lesions the rabies virus in spontaneous cases of rabies in ruminants and to determine the efficiency of the direct fluorescent antibody test (DFA), mouse inoculation (MI) and presence of Negri bodies in the diagnosis of the disease, 48 cases of the rabies were examined. Samples of frontal, temporal, parietal and occipital cerebral cortex, hippocampus, thalamus, rostral and caudal colliculi, cerebellum, pons, medulla oblongata, basal nuclei and sections of the cervical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
3
2
0
2
Order By: Relevance
“…Moreover, a bovine that died after a clinical course of 6 days in the current study had NBs only in the cerebellum. NBs developed more often in the cerebellum of cattle from the current study corroborating the findings from others (Langohr et al 2003, Silva et al 2010. However, in one bovine NBs were found only in the trigeminal ganglion.…”
Section: G1supporting
confidence: 92%
“…Moreover, a bovine that died after a clinical course of 6 days in the current study had NBs only in the cerebellum. NBs developed more often in the cerebellum of cattle from the current study corroborating the findings from others (Langohr et al 2003, Silva et al 2010. However, in one bovine NBs were found only in the trigeminal ganglion.…”
Section: G1supporting
confidence: 92%
“…Regarding the distribution of the lesion, the cerebellum was the best area for visualizing the corpuscle, similar to what was described by Wisser et al (2020), Silva et al (2010) and Langohr et al (2003). It is known that rabies does not infect all brain structures equally, thus varying the presence of NB with the analyzed area and thus compromising the diagnosis efficiency.…”
Section: Discussionsupporting
confidence: 75%
“…Studies have shown that the incubation period of the virus from herbivore samples inoculated in mice varies from 7 to 13 days (Silva et al, 2010;Achkar et al, 2010). Here, the virus was isolated in 75% of the samples, and the incubation period varied from 7 to 14 days.…”
Section: Discussionmentioning
confidence: 82%